2008
DOI: 10.1597/06-078.1
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Thresholds in Newborns with a Cleft Palate Assessed by Auditory Brain Stem Response

Abstract: The incidence of hearing loss in a cohort of cleft palate infants has been objectively estimated by auditory brain stem response thresholds and was found to be very high (82%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
0
31
0
2
Order By: Relevance
“…An English study utilized ABR to measure the incidence of hearing loss in infants with cleft palate only and found that 82% of the infants tested had hearing loss, and most of them had bilateral mild conductive hearing loss (Viswanathan, Vidler & Richard, 2008). Without consideration of conductive hearing loss, abnormal ABR responses in infants with cleft were rarely found in another study (Yang et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An English study utilized ABR to measure the incidence of hearing loss in infants with cleft palate only and found that 82% of the infants tested had hearing loss, and most of them had bilateral mild conductive hearing loss (Viswanathan, Vidler & Richard, 2008). Without consideration of conductive hearing loss, abnormal ABR responses in infants with cleft were rarely found in another study (Yang et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…ABR has been used on children with CL/P before 12 months of age, and it was found most children with CL/P showed mild to moderate conductive hearing loss at an early age (Hélias et al, 1988). Moreover, a UK study indicated more than 80% of infants with cleft palate (CP) had abnormal ABR responses, and most noted hearing loss was conductive, mild and bilateral (Viswanathan, Vidler & Richard, 2008). Aside from ABR, a series of studies conducted by researchers from the University of Helsinki used mismatch negativity (MMN) as an index to compare auditory cortical function between children with CL/P (both non-syndromic CL/P and CL/P with syndrome) and craniofacially normal children (Ceponiene et al, 2002; Ceponiene et al, 2000; Ceponiene et al, 1999; Cheour et al, 1999; Cheour et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, they did not compare their cleft palate patients with controls. Viswanathan et al [18] examined auditory brainstem responses in a retrospective case note study design and found hearing loss in 82% of the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the prevalence of conductive hearing loss among children without CLP is 12.9%. Although the likelihood of developing OME is reduced after reaching adulthood, it is estimated that 50% of these children suffer from permanent conductive hearing loss [21,22]. Additionally, 0.9-5.9% of patients with CLP develop primary acquired cholesteatoma, the probability of which is 100-200 times higher among those without CLP [23,24].…”
Section: Consequences Of Ome In Clpmentioning
confidence: 99%
“…Up to 90% of infants born with CLP suffer from OME before their first birthday [2]; therefore, it is recommended that otologic tests be conducted as soon as possible after birth to ascertain whether fluid has collected in the middle ear [21,32]. The use of a pneumatic otoscope is the fastest and most direct method used for the inspection of the eardrum for color and contour and determining whether fluid has collected in the middle ear.…”
Section: Examination and Diagnosismentioning
confidence: 99%